2020
DOI: 10.1038/s41598-020-62979-9
|View full text |Cite|
|
Sign up to set email alerts
|

Hypothermic Oxygenated New Machine Perfusion System in Liver and Kidney Transplantation of Extended Criteria Donors:First Italian Clinical Trial

Abstract: With the aim to explore innovative tools for organ preservation, especially in marginal organs, we hereby describe a clinical trial of ex-vivo hypothermic oxygenated perfusion (HOPE) in the field of liver (Lt) and kidney transplantation (Kt) from extended criteria Donors (ecD) after brain death. A matched-case analysis of donor and recipient variables was developed: 10 HOPE-ECD livers and kidneys (HOPE-L and HOPE-K) were matched 1:3 with livers and kidneys preserved with static cold storage (ScS-L and ScS-K). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 54 publications
3
65
0
1
Order By: Relevance
“…There were no changes in IL-2 production by CD8+ T cells after NMLP. Studies have identified that within the perfusate and liver tissue samples in both NMP and SCS there is a significant increase in regulatory T helper cells and regulatory cytokines implementing immune tolerance in liver grafts (65,67). We also see a statistically significant abundance of intrahepatic Tregs in NMP when compared to SCS (4.36% ± 3.27 vs. 1.9% ± 1.8, p = 0.0156), and in conjunction with the presence of IL-2 this promotes an expansion and proliferation of the Treg subset.…”
Section: Immune Response and Nmlpmentioning
confidence: 99%
“…There were no changes in IL-2 production by CD8+ T cells after NMLP. Studies have identified that within the perfusate and liver tissue samples in both NMP and SCS there is a significant increase in regulatory T helper cells and regulatory cytokines implementing immune tolerance in liver grafts (65,67). We also see a statistically significant abundance of intrahepatic Tregs in NMP when compared to SCS (4.36% ± 3.27 vs. 1.9% ± 1.8, p = 0.0156), and in conjunction with the presence of IL-2 this promotes an expansion and proliferation of the Treg subset.…”
Section: Immune Response and Nmlpmentioning
confidence: 99%
“…Machine perfusion is increasingly used to preserve kidneys and it provides an excellent opportunity to examine the kidney before transplantation 20 , 21 . In the present study, we confirmed that grafts release EC after perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…As for the case of SCS, HMP slows down the cell metabolism, reducing oxygen requirements and ATP depletion. Additional research focuses on a vasoprotective effect of HMP, by potentially maintaining the hemodynamic stimulation of the endothelium, decreasing the vasospasm, facilitating the expression of protective flow dependent genes and maintaining the patency of the vascular bed [ 30 , 31 , 32 ]. In this respect, the use of pulsatile flow in HMP appears to be the important factor in HMP effects versus non-pulsatile flow, in order to ensure benefits of HMP compared to SCS [ 6 ].…”
Section: Preservation Techniquesmentioning
confidence: 99%